Online mindfulness-based cognitive therapy for treatment-resistant depression: a parallel-arm randomized controlled feasibility trial - Rodrigues, Michele Ferreira; Quagliato, Laiana; Appolinario, Jose Carlos; Nardi, Antonio E. (Frontiers in Psychology, 2024)
Introduction Treatment-resistant depression (TRD) presents a significant challenge, affecting approximately 30% of individuals diagnosed with major depressive disorder and leading to poor treatment responses. Innovations in digital mental health, especially online mindfulness-based cognitive therapy (eMBCT), offer promising avenues for enhancing access to effective mental health care for individuals with TRD in a clinical setting. Objective The aim of this study was to examine the feasibility of eMBCT in an individual clinical context to decrease depressive symptoms for TRD. Methods Conducted at the Institute of Psychiatry of the Federal University of Rio de Janeiro, Brazil, this parallel-arm, randomized controlled feasibility trial involved outpatients diagnosed with TRD, aged 18 and above. Of the 39 outpatients invited, 28 were randomized into two groups: an intervention group receiving the eMBCT program (n = 15) and a control group (n = 13). The intervention, consisting of an 8-week course, was delivered via live video sessions. Following the assessment period, participants in the control group were offered the eMBCT intervention. Assessments using standardized questionnaires were conducted at the start and end of the study. Results Within the eMBCT group, improvements were observed in depression symptoms (Z = −3.423; p = 0.001; effect size r = 0.78), anxiety symptoms (Z = −3.361; p = 0.001; effect size r = 0.77), with no significant changes in the control group. Comparatively, the eMBCT group showed significant reductions in depression symptoms and improvements in clinical global impressions over the control group (BDI2: U = 30.5; p = 0.015; effect size r = 0.47, CGI1: U = 21.0; p = 0.004; effect size r = 0.56). Conclusion eMBCT in an individual format combined with medication, appears to be a feasible treatment for TRD, decreasing symptoms of depression. In a future trial the control group may have a manualized intervention. Clinical trial registration The Brazilian Clinical Trials Registry: (https://ensaiosclinicos.gov.br/rg/RBR-6zndpbv) and RBR-6zndpbv.